Advancing Interprofessional Education and Collaborative Practice: outcomes of the AFREhealth-FAIMER Student Elective Exchange Program in Health Professions Education in Africa - Nawagi, Faith; Vyas, Rashmi; Kiguli Malwadde, Elsie; Yuan, Shiyao; Bedoll, Deborah; Adejumo, Prisca Olabisi; Phimister, Rory; Drendall, Julie; Seeling, Justin; Suleman, Fatima (Frontiers in Medicine, 2025)
BackgroundWhile some African health professions institutions have advanced in integrating Interprofessional Education and Collaborative Practice (IPECP) into their curricula, many still struggle with traditional, siloed training. To address this gap, the African Forum for Research and Education in Health (AFREhealth), partnering with FAIMER, a division of Intealth, developed the AFREhealth-FAIMER IPECP Student Elective Exchange Program (IPECP Program). This study assessed the IPECP competencies of participating students and gathered stakeholder perspectives on the IPECP Program.MethodsThe 2018 revised Interprofessional Collaborative Competency Attainment Scale (ICCAS), containing 21 items, was used to assess student participants’ IPECP competencies before and after participating in the IPECP Program. Paired sample T-tests were run to examine if there was a significant improvement in IPECP competencies after students participated in the program, on both the total and item score levels. The study also administered online surveys to collect feedback from faculty and managers of the IPECP Program on its design, implementation, benefits, and challenges.ResultsStudents reported a significant improvement in IPECP competencies after participating in the program, with the mean ICCAS total score rising from 79.27 (±12.24) pre-training to 85.63 (±8.75) post-training (t(179) = 7.48, p < 0.005). All faculty participants (100%, n = 18) indicated that country-specific case studies facilitated teaching IPECP skills through virtual delivery. Additionally, 6 out of 18 program managers noted that this program marked their institution’s first engagement in virtual IPECP electives. All faculty (n = 18) and managers (n = 10) who responded to the survey thought the IPECP program enhanced regional collaborations and global exposure and equipped the students with cross-country IPECP skills. Internet connectivity was a cross-cutting challenge among faculty and managers given the virtual nature of the program.Discussion and conclusionsThe student participants of the IPECP Program self-reported enhanced IPECP competencies, fostering an understanding of the various population health issues in multiple African countries. The findings suggest that faculty-guided, country-specific case studies may offer a viable strategy for implementing IPECP during international electives using a virtual mode of delivery.